Acute effects of high intensity interval training with step aerobics training on cognitive performance in male futsal players - Bumrung, N; Jansupom, C; Rohmansyah, N; Khaothin, T; Phonthee, S; Hiruntrakul, A. (Journal of Human Sport & Exercise, 2025)
Previous studies have shown that success in sports, especially futsal is linked to higher levels of cognitive functioning. It is widely recognized that short-term, high intensity interval training exercise enhances cognitive function. Nevertheless, the impact of short-term, high-intensity aerobic exercise combined with step aerobics on cognitive function remains unclear. Thus, we aimed to evaluate the acute effects of sport-specific high-intensity interval training with step aerobics training on cognitive in professional futsal players. Here we assess cognitive performance before and after engagement in a high-intensity interval training with step aerobics exercise (HIITSA) regimen. Fifteen male futsal players aged 18-22 years were randomly assigned to one of two experimental groups: (a) an acute high-intensity with step aerobics exercise (n = 8) or (b) a non-exercise control (n = 7). Our findings show that participants in the exercise group demonstrated enhanced performance in cognitive processing tasks (p = .05). In contrast, control participants who did not engage in exercise showed no significant change over time in cognitive performance (p = .05). Additionally, we observed that there was no significant muscle hypertrophy following the HIITSA training over a 4-week period (p = .05). In conclusion, indicate that a brief training period incorporating HIITSA sessions promoted as a time-efficient enhance cognitive performance in elite young futsal players.